Millennials in architecture : generations, disruption, and the legacy of a profession - Sollohub, Darius (University of Texas Press, 2019)
Much has been written about Millennials, but until now their growing presence in the field of architecture has not been examined in depth. In an era of significant challenges stemming from explosive population growth, climate change, and the density of cities, Millennials in Architecture embraces the digitally savvy disruptors who are joining the field at a crucial time as it grapples with the best ways to respond to a changing physical world. Taking a clear-eyed look at the new generation in the context of the design professions, Darius Sollohub begins by situating Millennials in a line of generations stretching back to early Modernism, exploring how each generation negotiates the ones before and after. He then considers the present moment, closely evaluating the significance of Millennial behaviors and characteristics (from civic-mindedness to collaboration, and time management in a 24/7 culture), all underpinned by fluency in the digital world. The book concludes with an assessment of the profound changes and opportunities that Millennial disruption will bring to education, licensure, and firm management. Encouraging new alliances, Millennials in Architecture is an essential resource for the architectural community and its stakeholders